Sub harmonic oscillations in first order systems with delay - Anh, Nguyen Dong; Khiem, Nguyen Tien (Vietnam Journal of Mechanics, 1990)
The sub harmonic oscillations with frequency, which is n times smaller than that of exciting periodic force, in first order systems with delay are studied. The averaging equations for the am altitude and phase of the response are constructed. A detailed research of third order sub harmonic oscillation in the Duffing system is given.